Entrepreneurial Marketing and Customer Value Creation: The Mediating Roles of Technology, Customization, and Customer Orientation Under Varying ‎Customer Complexity - Sam, Toong Hai; Mu'min, Halek; Wahyudono , Denny Bernardus Kurnia; Darmanto (International Journal of Accounting and Economics Studies, 2025)
The current study focuses on the interrelations between entrepreneurial marketing (EM), technology customization (TC), customer ‎orientation (CO), and customer satisfaction (CS), incorporating customer complexity (CC) as a moderating variable. The study builds and ‎empirically tests an integrated framework using data from 279 tech-based firms across diverse industries, leveraging resource-based ‎view and dynamic capabilities theories. Entrepreneurial marketing positively affects customer satisfaction both directly and indirectly ‎through technology customization, product innovation, and customer orientation, as shown by structural equation modeling. These ‎relationships are moderated ( in a positive sense) by customer complexity, which enhances the effects of entrepreneurial marketing on ‎technology customization and the effect of technology customization, respectively, on customer orientation. Theoretical implications of ‎these findings advance research on entrepreneurial marketing with practical implications for technology-based firms aiming to increase ‎customer satisfaction in ever more complex market contexts‎.
Keywords: Entrepreneurial Marketing; Technology Customization; Customer Orientation; Customer Satisfaction; Product Innovation; Customer ‎Complexity.